Pouvoir antioxydant et antibactérien d’Acacia arabica vis à vis de quelques bactéries pathogènes d’origine alimentaire - HAMDI CHERIF, SAFIA (My University, 2023)
In this study, we were interested in the extraction and assay of active compounds (polyphenols) from the pods and seeds of Acacia arabica, a plant known for its use in traditional medicine and located in southern Algeria. The extraction of oil from the seeds was also part of the study. Antimicrobial activity was also tested using hydroalcoholic and aqueous extracts of the plant studied. The results of these extractions showed that the ethanol: water solvent gave a higher yield (68% for the seeds and 39% for the pods) whereas extraction with distilled water presented relatively low values (16%, 36% and 10%) for the seeds, pods and mixture respectively. It was possible to obtain a vegetable oil from Acacia arabica using a Soxhlet method and required follow-up purification. The highest oil extraction yield was obtained using hexane (2.16%). The polyphenol concentrations obtained by the ethanolic extract were (168.09 and 100.09) mg EAG/g dm for seeds and pods respectively. The aqueous extract gave low concentrations (61.36 and 43.9) mg EAG/g dm. The antioxidant activity was significantly higher with the ethanolic extract than with the aqueous extract. The results obtained led to an understanding of the antibacterial effect of this plant's polyphenols in relation to a number of pathogenic strains. The hydroethanol extract of the pods in particular showed excellent antimicrobial power against the strains tested: Escherichia coli, Pseudomonas aeruginosa, Candida albicans, Staphylococcus aureus and Bacillus Creus, with inhibition areas varying between 12 and 17 mm. In the same experimental protocol, inhibition areas of 11 to 15 mm were recorded for the aqueous extract. Crude oil extracted from Acacia arabica seeds had no inhibitory effect on the strains studied
Keywords: Acacia arabica; Polyphenols; Solvent; Antibacterial activity; Antioxidant activity; Pathogenic strains